Densifying the future : a critical review of osseodensification and implant dentistry - Ortiz, Rafael Guizzo Gonzalez (My University, 2025)
Osseodensification has established itself as an innovative surgical approach in implantology, permitting bone compaction without the removal of tissue and thereby diverging from the principles of conventional subtractive drilling techniques (Huwais & Meyer, 2016). By employing specially designed burs in reverse rotation, the method preserves autogenous bone particles, increases insertion torque and enhances primary implant stability. The technique fosters the formation of new bone and elicits a more efficient biological response4factors that are critical for predictable osseointegration, particularly in anatomically challenging regions such as the posterior maxilla (Cardozo et al., 2018). Evidence suggests that osseodensification allows the adoption of immediateloading protocols with greater safety, improves local vascularisation and accelerates healing through the induction of controlled micro-fractures (Macari et al., 2024). Diagnostic tools such as computed tomography facilitate precise surgical planning and thereby reduce operative risks. The technique is further associated with increased periimplant bone density and a reduced risk of mechanical and biological complications (Lahens et al., 2016). Notwithstanding these advantages, limitations remain regarding the learning curve, variability in operative parameters and the influence of systemic factors such as smokings and osteoporosis. Standardising the technique therefore continues to represent a significant challenge. Comparative studies report success rates comparable with traditional methods, albeit with demonstrable advantages in initial stability (Stacchi et al., 2022). Nonetheless, uncertainty persists concerning the long-term maintenance of these gains. In this context, osseodensification stands out as a promising technique in contemporary clinical practice; however, further multicentre and longitudinal investigations are required to achieve definitive validation of its protocols and benefits.
Dissertação para obtenção do grau de Mestre no Instituto Universitário Egas Moniz
Keywords: Osseodensification; Dental implants; Bone densification; Implantology